Analysis of perceptions of managerial skills in the public sector (GEON Journal (Management, Organizations and Business), 2025)
Problematic: The lack of development of managerial skills in the public sector can have serious consequences, affecting the effectiveness of management, innovation, motivation, accountability, transparency, and government legitimacy. Therefore, it is crucial to invest in leaders capable of facing the current challenges of the public sector. Objectives: To analyze the perception of managerial skills, such as leadership, communication, motivation, emotional intelligence, and teamwork, with the aim of evaluating their importance in the public sector. Materials and methods: A descriptive, cross sectional, and correlational study was conducted among public servants of a governmental department in Veracruz. A questionnaire was used as a data collection tool, administered through Google Forms. A validated instrument to measure five dimensions of managerial skills was sought and used. The collected data were processed in SPSS V25 to obtain correlations between the identified dimensions. Results and discussion: The study found a weak positive correlation between leadership and teamwork. Additionally, very weak correlations were observed between leadership and communication, as well as between leadership and motivation. Surprisingly, no significant correlation was found between leadership and emotional intelligence. These results indicate that, in the dataset analyzed, the relationship between leadership and the other measured variables is mostly weak, with some correlations even being insignificant. Conclusions: The findings highlight the importance of considering other managerial skills besides leadership and suggest that factors not explored in this study could have a significant impact on these variables.Contribution/originality: This study contributes to subnational analysis by being one of the first to examine managerial skills in a department of the Government of the State of Veracruz, emphasizing their importance and effects on the perception of public servants.
Keywords: leadership; organizational communication; work motivation; emotional intelligence; teamwork